Determinación de la capacidad de almacenamiento en un puerto marítimo considerando el flujo en unidades de carga - Concepción Fanego, Manuel C (Ingeniería, 1999)
The external trade constitutes in any country a fundamental economic element. It is executed in great measure by means of the ports. The warehouse of a port makes a spring action between the flow of arrival of loads and the exit of the same ones. In this article is determined the necessary capacity of roofed storage in a marine port considering the flow in load units. A mathematical-statistical model thinks about to solve the problem with fictitious data of a small conventional port.